Coordination Insertion Mechanism of Ring‐Opening Polymerization of Lactide Catalyzed by Stannous Octoate†. Issue 7 (27th May 2021) - Rao, Weihan; Cai, Caiyun; Tang, Jingyu; Wei, Yiman; Gao, Caiyun; Yu, Lin; Ding, Jiandong
Main observation and conclusion: Ring‐opening polymerization (ROP) of cyclic esters in the presence of stannous octoate (Sn(Oct)2 ) is the main way to obtain biodegradable aliphatic polyesters, an important family of biodegradable polymers which have been widely used and still rapidly developed in the fields of biomedical polymers and environment‐friendly materials. The underlying mechanism is thought via a coordination‐insertion way, but the pathway is still open owing to the absence of direct experimental evidence. Herein, we inquire this issue through density functional theory (DFT) calculations. According to our DFT calculations and the following Curtin‐Hammett evaluation, the carbonyl oxygen has a significant advantage over the ester oxygen, and thus the ring is opened mainly through pathway A instead of pathway B. The stannous octoate is identified as a catalyst rather than an initiator. We eventually summarize the main stages during the whole polymerization of lactide. Abstract : This work employs the density functional theory to deal with eight geometry types of monomer and trigger complex through two pathways of catalysis reaction to proceed the ring‐opening polymerization of lactide leading to the identical polymer product. The ring‐opening mechanism is revealed, and the whole polymerization process is summarized.